When Bacterial Culture Fails, Metagenomics Can Help: A Case of Chronic Hepatic Brucelloma Assessed by Next-Generation Sequencing - Lazarevic, Vladimir; Gaïa, Nadia; Girard, Myriam; Leo, Stefano; Cherkaoui, Abdessalam; Renzi, Gesuele; Emonet, Stéphane; Jamme, Sharon; Ruppé, Etienne; Vijgen, Sandrine; Rubbia-Brandt, Laura; Toso, Christian; et al. (Frontiers in Microbiology, 2018)
Here, we sequenced DNA extracted from a necrotic hepatic lesion from a patient with suspected chronic hepatic brucelloma but negative culture results. Although most of the taxonomically-classified sequencing reads corresponded to human genome sequences, our data suggest that whole metagenome shotgun sequencing may be used together with other tests to strengthen the diagnosis of hepatic brucelloma.